Repeat syphilis has a different immune response compared with initial syphilis: an analysis of biomarker kinetics in two cohorts. (11th October 2017) - Kenyon, Chris; Tsoumanis, Achilleas; Osbak, Kara; Van Esbroeck, Marjan; Florence, Eric; Crucitti, Tania; Kestens, Luc
Abstract : Objective: We aimed to asses if there are differences in the clinical presentation and immune response of repeat as compared with initial syphilis. Methods: Prospective study: we prospectively recruited all patients with a new diagnosis of syphilis and tested their plasma for a range of cytochemokines and rapid plasma reagin (RPR) at baseline pretreatment and 6 months following therapy. Retrospective study: we compared RPR assay response kinetics between initial and repeat syphilis in persons attending our HIV/STI clinic from 1993 to 2016. Results: Prospective study: a total of 91 individuals, 36 with initial syphilis and 55 with repeat syphilis, were included in the study. At baseline visit, those with initial syphilis were more likely to be symptomatic and have higher levels of interleukin-10 than repeaters. At baseline, median RPR titres were higher in the repeat than the initial infection groups. Repeaters were less likely than those with initial infections to serorevert to a negative RPR and be serofast (<4-fold RPR titre decline) at 6 months. Retrospective study: syphilis was diagnosed in 1027/43 870 individuals tested. At diagnosis, repeaters had higher RPR titres and a stepwise increase in RPR titre with number of syphilis episodes. They had a different RPR test response kinetic: they were less likely to be serofast and to serorevert than initial syphilis at 6 and 12 months. No individuals with four or more previous episodes of syphilis seroreverted. Conclusion: Repeat syphilis has a different clinical presentation and immunological response to initial infection.